Rent seeking in hierachical firms - Gil S. Epstein; Ira N. Gang (Rutgers University, Department of Economics, 2002)
Hierarchical firms are enterprises with rigid internal job ladders. We examine the state enterprise as the prototypical hierarchical firm. In the state enterprise, promotion of employees through the internal hierarchy is determined by the workers' allocation of time between rent seeking and productive activity. Our model shows that given the incentive structure of the state enterprise we tend to see less productive and more adept rent seekers at senior management positions in such firms. Moreover, as we move up the firm's hierarchy, a decline in the productivity levels of the workers will be observed.
Keywords: D2; D72; L32; 330; hierarchical firms; internal job ladder; promotion; rent-seeking; state enterprise; Unternehmensorganisation; Erwerbsverlauf; Öffentliches Unternehmen; Leistungsmotivation; Rent Seeking; USA